Molecular Characterization of Human Leukocyte Antigen Haplotypes in Coeliac Disease: Evidence from Libyan Patients - Daeki, Ali; Gibreel, Tarek; Ben-Darif, Elloulu; Ben-Darif, Amal; Al-Salimi, Haytham; Albeshte, Ahmed; Elzaroug, Aisha (AlQalam Journal of Medical and Applied Sciences, 2025)
Coeliac disease (CD) is a complex condition characterized by chronic inflammation of the small intestine, triggered by gluten ingestion in genetically predisposed individuals. This study aimed to understand the genetic factors influencing CD and to evaluate the role of the Human Leukocyte Antigen (HLA) alleles in the different clinical manifestations of coeliac patients. The study was conducted between 2015 and 2019, involving 24 patients previously diagnosed serologically and histopathologically with CD, aged 1-45 years. Blood samples were collected, and extracted DNA was amplified using the AllSet+™ Gold SSP Kit. Screening for HLA class I (A, B, C) and class II (DQB, DRB) loci. The study showed the presence of multiple alleles at the DQB1 and DRB1 loci, which are well-established markers for CD susceptibility. Only three DQB1 alleles were detected among the tested coeliac patients, with 87.5% carrying the HLA-DQ2 (HLA-DQB1*02) haplotype. Whereas, for DRB1 loci 50% of the patients carried HLA-DRB1*03. The study also found that only three HLA-DRB3 alleles were detected, with HLA-DRB3*01 as the dominant allele (79.1%). The HLA-DQ2 is the most common HLA allele in Libya plays a significant role in CD. The HLA-DQ2 haplotype, a combination of HLA-DQB1*02, accompanied by HLA-DRB1*03 and HLA-DRB3*01, is the genetic risk factor for Libyan CD cases. The high prevalence of the HLA-DQB1*02 allele indicates a need for increased awareness and screening.